Desarrollo de un software educativo del bloque 1 “las poblaciones iniciales del Ecuador” para la asignatura de ciencias sociales como herramienta de apoyo para el proceso de enseñanza-aprendizaje para el sexto año de educación general básica de la unidad educativa municipal “HÉROES DEL CENEPA” de la ciudad de Loja - Ortega Rojas, Byrón Mauricio (2015)
This research has as its theme the "EDUCATIONAL SOFTWARE DEVELOPMENT OF A ONE BLOCK" INITIAL STOCKS ECUADOR "FOR THE COURSE OF SOCIAL SCIENCE AS A TOOL TO SUPPORT THE PROCESS OF LEARNING FOR THE SIXTH YEAR OF BASIC EDUCATION GENERAL MUNICIPAL EDUCATIONAL UNIT "CENEPA HEROES" IN THE CITY OF LOJA. The central problem is that the methodology used by the teacher is inadequate because it is still kept in classical methodologies such as the dictation, and he alone is the imparting of knowledge, and this turns into system tired classes and anything productive so they had to change the methodology to make it more participatory and thus achieve a dynamic environment that will help students to be generators and imparting their own knowledge. Whose overall objective is to develop an educational software that supports the teaching-learning process, to the subject of social sciences for the sixth year of basic education in the municipal education unit "Heroes Cenepa" of the city of Loja, in order that students go to the forefront of technology and that they generate their own knowledge. The methods used in the research process were the inductive method, deductive method, scientific method, analysis, synthesis and statistical, and techniques such as the interview survey and direct observation, the people with whom I was working was a total of 35 students including 20 men and 15 women. The results achieved based on the evaluation form indicated that educational software is feasible within the teaching-learning process with 100% stated that generates an environment conducive to the development of significant knowledge and 100% of students indicated that it is technically correct to learn Social Sciences.